PEMANFAATAN LIMBAH KELAPA SAWIT (TANDAN KOSONG KELAPA SAWIT) SEBAGAI PUPUK ORGANIK YANG RAMAH LINGKUNGAN DI KABUPATEN LABUHAN BATU UTARA - Abdurrozzaq Hasibuan; Qori Fauziah Nur Nasution, Annisa Mutiara Putri Lubis, Annisah Ariani Harahap; Suhela Putri Nasution (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
Palm oil waste is a waste or by-product produced during the palm oil processing process. During the palm oil extraction process, some parts of the oil palm fruit are not used and are considered waste. The use of empty coconut bunches as agricultural organic fertilizer is an interesting topic in the field of sustainable agriculture. Empty coconut bunches are waste generated from the palm oil industry, and can be converted into organic fertilizer which is beneficial for increasing soil fertility and crop productivity. The use of empty coconut bunches as organic fertilizer also has environmental benefits. By processing this waste into fertilizer, empty coconut bunch waste can be reduced, thereby reducing its negative impact on the environment in North Labuhan Batu Regency. In addition, the use of organic fertilizers reduces dependence on chemical fertilizers that can pollute soil and water. This research uses literature studies, the object in this study is information systems and previous research related to the phenomena discussed, this aims to develop solutions and related problems. The results showed that organic fertilizer from empty coconut bunches has reduced environmental pollution of greenhouse gases. This organic fertilizer helps reduce fertilization costs from farmers' dependence on chemicals. In addition, EFB also contains a number of important nutrients such as nitrogen (N), phosphorus (P), potassium (K) and magnesium (Mg) which can delight the soil. Organic fertilizers derived from EFB have an additional advantage, namely releasing nutrients slowly into the soil thereby reducing the risk of environmental pollution and increasing the efficiency of nutrient use